Makna Kesetaraan Gender dagi Followers Instagram @wmnlyfe - Karnanto, Natasya Yolanda Poetri; Utamidewi, Wahyu; Nurkinan, Nurkinan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The issue of gender equality is one of the issues that still often occurs, especially in Indonesia. One of the things that underlies this gender inequality occurs because of the inherent patriarchal culture which shows that men tend to hold greater power roles so that it indirectly degrades the existence of women. In order to be free from the oppressive patriarchal culture, men's participation is also considered necessary in an effort to increase public awareness about gender equality. The involvement of mass media, namely Instagram, is also able to play a considerable role in efforts to voice issues regarding gender equality. The research method used is a descriptive qualitative method with in-depth interviews with informants who are followers of @wmnlyfe. The results of this study will explain how individuals interpret gender equality contained in the campaign video "Women Can Be Safe Where" by relating it using the theory of social reality construction based on three dialectical stages, namely externalization, objectivation, and internalization. Through the "Women Can Be Safe Where" campaign published by @wmnlyfe's Instagram account, it can be said that the campaign video succeeded in conveying the meaning of gender equality to its followers. By promoting the values of equality, this account provides insight into the importance of respecting and respecting gender differences in society. Keywords: Gender Equality, Social Reality Construction, Meaning of Gender Equality, Instagram